2003
DOI: 10.1038/sj.ijir.3900982
|View full text |Cite
|
Sign up to set email alerts
|

Morphological modifications in clitoris and vagina in spontaneously hypertensive rats

Abstract: We evaluated possible morphological alteration in clitoris and vagina from spontaneous hypertensive rats (SHR) and normotensive WKY rats. Clitoris and vagina were processed by Masson's trichrome, anti-a-smooth-muscle actin, anticollagen type I (COL I) and type III (COL III), and anti-TGFb 1 . SHR presented higher amount of clitoral cavernous smooth muscle (CSM), vascular smooth muscle; TGFb 1 in clitoral vessel wall; higher wall/lumen ratio in both vaginal and clitoral vessels; and remarkable interstitial fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 17 publications
3
16
0
Order By: Relevance
“…The fibrosis that we observed in vaginal tissue from type 1 diabetic rats appears to be similar to that seen in vaginal tissue from spontaneous hypertensive rats (12), sex hormonedeprived rabbits (9 -11, 13), and rabbits with atherosclerotic lesions and high cholesterol (22) as well as in clitoral tissue from alloxan-induced diabetic rabbits (21,22). All these conditions are associated with the reduction of the smooth muscle content, the impairment of the hemodynamic mechanisms regulating blood flow, and the loss of tissue compliance.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The fibrosis that we observed in vaginal tissue from type 1 diabetic rats appears to be similar to that seen in vaginal tissue from spontaneous hypertensive rats (12), sex hormonedeprived rabbits (9 -11, 13), and rabbits with atherosclerotic lesions and high cholesterol (22) as well as in clitoral tissue from alloxan-induced diabetic rabbits (21,22). All these conditions are associated with the reduction of the smooth muscle content, the impairment of the hemodynamic mechanisms regulating blood flow, and the loss of tissue compliance.…”
Section: Discussionsupporting
confidence: 74%
“…Similar alterations occur in the clitoris, leading to hemodynamic compromise in both organs (9,11). Clitoral and vaginal fibrosis also is associated with hypertension in the rat (12) and with increasing age (13).…”
mentioning
confidence: 84%
“…Balloon injury of aorto-iliac arteries and a high cholesterol diet has been shown to result in an increased clitoral fibrosis and an impairment of vaginal and clitoral engorgement [69,75]. Morphological characterization of clitoral and vaginal tissue revealed that in the spontaneously hypertensive rat (SHR) there is an increase in smooth muscle and fibrosis, relative to a normotensive strain [76]. In addition, SHR have reduced apomorphine-induced sexual responses as compared to normotensive strains (our unpublished observations).…”
Section: Etiologies Of Female Sexual Dysfunction: Focus On Cardiovascmentioning
confidence: 74%
“…The rat clitoris has been investigated in functional studies measuring clitoral relaxation mediated by a nitric oxide donor and cyclic guanosine monophosphate analog [35]. Additionally, clitoral morphological changes have been observed in spontaneously hypertensive rats [36], supporting clinical observations linking FSD and cardiovascular diseases, such as hypertension [23,37]. Clitoris from both rats and humans share similar innervation and vasculature [34], therefore studying rat sexual responses in these specific arteries is indeed a practical application for the study of FSD.…”
Section: Discussionmentioning
confidence: 99%